AN ANALYSIS OF COMMUNICATION STRATEGIES IN INSTAGRAM CAPTIONS ON THE @MISSHIJABSUMATERAUTARA ACCOUNT - Winda Kustiawan; Rara Ardina Khairi; Rashin Salsabila; Muhammad Panusunan Harahap (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the textual and visual message design in Instagram social media posts as a form of identity representation and public communication strategy. The research focuses on the @misshijabsumaterautaraa account, which consistently produces content themed around Muslim women, digital da'wah, and Islamic social values. Using a qualitative approach with content analysis methods, data were collected through documentation of posts and participatory observation conducted from January to April 2025. The findings reveal that the message design on this account integrates visual symbols, religious narratives, and participatory strategies to construct the image of the ideal Muslim woman: devout, modern, and communicative. Caption texts and visual elements work synergistically to build identity narratives, convey values, and encourage audience engagement within an online community. These findings affirm that social media functions not only as a medium of communication but also as a symbolic space rich in ideological meaning and social representation. This study contributes to the development of digital visual communication studies, particularly in the context of da'wah and identity formation in the era of new media.